2016
DOI: 10.1111/jocs.12873
|View full text |Cite
|
Sign up to set email alerts
|

Histologic alterations in tetralogy of Fallot

Abstract: Pre-existing cardiomyocyte injury accompanied by mitochondrial damage and fibrosis were more pronounced in cyanotic TOF patients. Early repair may prevent the development of histopathologic alterations in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…Indeed SHG signal is of big interest for the characterization of myocardial pathologies especially fibrotic remodeling. SHG very sufficiently visualizes disorganized collagen-rich structures characteristic for progressing fibrosis in the transmural images and also in the cross sections where anincrease of extra cellular matrix between myocyte bundlesis observed as reported for myocardial disease [26] .…”
Section: Resultssupporting
confidence: 54%
“…Indeed SHG signal is of big interest for the characterization of myocardial pathologies especially fibrotic remodeling. SHG very sufficiently visualizes disorganized collagen-rich structures characteristic for progressing fibrosis in the transmural images and also in the cross sections where anincrease of extra cellular matrix between myocyte bundlesis observed as reported for myocardial disease [26] .…”
Section: Resultssupporting
confidence: 54%
“…In terms of evolution of myocardial fibrosis, the finding of severe fibrosis in patients with long aortic cross-clamp time during primary repair points to the vulnerability of the myocardium to irreversible damage during cardiopulmonary bypass and is consistent with previous reports 20–22. Although exposure to chronic hypoxia is known to be associated with severe myocardial fibrosis,23 in our population, collagen volume fraction was not associated with prior aortopulmonary shunt or age at primary repair.…”
Section: Discussioncontrasting
confidence: 58%
“…Hypoxia and RVOT obstruction lead to pathological changes such as RV hypertrophy and myocardial interstitial fibrosis ( 16 ). Chronic hypoxia is a major stimulus for myocardial remodelling and causes detrimental histopathological alterations in cardiac myocytes and fibrosis ( 13 , 17 ). Previous studies have shown varying degrees of histopathological changes and mild fibrosis in muscle specimens from TOF patients ( 11 , 18 ).…”
Section: Discussionmentioning
confidence: 99%